Single- and two-level osteotomy for the treatment of thoracolumbar kyphosis in ankylosing spondylitis patients with concomitant coronal malalignment - Jie Cheng; Tao Xu; Maierdan Maimaiti; Rui Cao; Chuanhui Xun; Weidong Liang; Weibin Sheng (Journal of Orthopaedic Surgery and Research)
Abstract Purpose To investigate the influence of apical vertebrae difference (AVD) on surgical decision-making and clinical outcomes of single- and two-level osteotomy in ankylosing spondylitis (AS) thoracolumbar kyphoscoliosis with sagittal and coronal imbalance. Methods A total of 27 AS patients with thoracolumbar kyphoscoliosis were enrolled in the study. Patients were divided into single- and two-level osteotomy groups based on the number of osteotomy levels. Coronal, sagittal, and clinical parameters were measured preoperatively, postoperatively, and at the last follow-up. AVD, operation time, blood loss, fused segments and complications were recorded between the two groups. Results Among 27 patients, 11 underwent single-level osteotomy and 16 underwent two-level osteotomy. The operation time, blood loss and number of fused segments were lower in single-level group compared to the two-level group (P < 0.001). Coronal, sagittal, and clinical parameters improved significantly after surgery (P < 0.05), with only osteotomized vertebral angle (OVA) showing a significant difference between the two groups (P < 0.05). The average AVD was 1.50 segments in single-level group and 3.30 segments in two-level group. Additionally, single- and two-level osteotomy accounted for 80% and 20% in group A, 77.8% and 22.2% in group B, and 0% and 100% in group C, respectively. Conclusion AVD was a crucial parameter in determining whether single- or two-level osteotomy was appropriate for AS patients with thoracolumbar kyphoscoliosis. If the AVD was < 3 segments, single-level osteotomy should be considered. If the AVD was ≥ 3 segments, two-level osteotomy was recommended.